Inoculation of the Leishmania infantum HSP70-II Null Mutant Induces Long-Term Protection against L. amazonensis Infection in BALB/c Mice - Manuel Soto; Laura Ramírez; José Carlos Solana; Emma C. L. Cook; Elena Hernández-García; José María Requena; Salvador Iborra (Microorganisms, 2021)
Leishmania amazonensis parasites are etiological agents of cutaneous leishmaniasis in the New World. BALB/c mice are highly susceptible to L. amazonensis challenge due to their inability to mount parasite-dependent IFN-γ-mediated responses. Here, we analyzed the capacity of a single administration of the LiΔHSP70-II genetically-modified attenuated L. infantum line in preventing cutaneous leishmaniasis in mice challenged with L. amazonensis virulent parasites. In previous studies, this live attenuated vaccine has demonstrated to induce long-protection against murine leishmaniasis due to Old World Leishmania species. Vaccinated mice showed a reduction in the disease evolution due to L. amazonensis challenge, namely reduction in cutaneous lesions and parasite burdens. In contrast to control animals, after the challenge, protected mice showed anti-Leishmania IgG2a circulating antibodies accompanied to the induction of Leishmania-driven specific IFN-γ systemic response. An analysis performed in the lymph node draining the site of infection revealed an increase of the parasite-specific IFN-ϒ production by CD4+ and CD8+ T cells and a decrease in the secretion of IL-10 against leishmanial antigens. Since the immunity caused by the inoculation of this live vaccine generates protection against different forms of murine leishmaniasis, we postulate LiΔHSP70-II as a candidate for the development of human vaccines.